2019
DOI: 10.11648/j.ijcm.20190301.11
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Role of p53 and Ki 67 Immunohistochemistry in Evaluation of Urinary Bladder Carcinomas in Egyptian Patients

Abstract: Background: Urothelial carcinomas (UC) are the most common cancers of urinary bladder responsible for a significant proportion of cancer morbidity and mortality. In Egypt, bladder cancer is the second most common malignancy. We did the present investigation to exhibit the clinicohistopathological highlights and to associate the p53 and Ki 67 immunoexpression with grade and stage of bladder carcinomas. Materials and Methods: sixty-two cases of bladder neoplasm were investigated. Grading and staging was done. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…In pT1 stage, Ki-67 expression was variable from low to high intensity, as well as in the pT2 stage. Similar results were found in Ali Mohammed et al study, but it should be mentioned that the study included twice as much patients [26]. As Ki-67 is a cell cycle and proliferation regulative protein, it is probably capable of predicting tumor behavior based on histological grading and staging.…”
Section: Discussionsupporting
confidence: 83%
“…In pT1 stage, Ki-67 expression was variable from low to high intensity, as well as in the pT2 stage. Similar results were found in Ali Mohammed et al study, but it should be mentioned that the study included twice as much patients [26]. As Ki-67 is a cell cycle and proliferation regulative protein, it is probably capable of predicting tumor behavior based on histological grading and staging.…”
Section: Discussionsupporting
confidence: 83%
“…It was observed that 31 (54.4%) patients had high grade carcinoma and 26 (45.6%) patients had low grade carcinoma. Mohamed in his study found 79% high grade and 21% low grade tumor 20 . Chinnasamy et al observed 63.5% high grade and 36.5% low grade carcinoma 18 .…”
Section: Resultsmentioning
confidence: 89%
“…Chou et al (2013) also found 59.5% MIBC and 40.5% NMIBC 21 . On the other hand, Mohamed found 72.6% NMIBC and 25.8% MIBC 20 . Xu et al found 69.4% NMIBC and 30.6% MIBC 1 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation